Critical realist accounting research: In search of its emancipatory potential. (January 2017) - Modell, Sven
Abstract: Over the past decade, a growing body of accounting research explicitly informed by critical realism has started to emerge and be deployed to diverse research tasks. Although the majority of this research lacks a clearly articulated emancipatory intent, several commentators have recently singled out critical realism as a promising way forward for critical accounting research. This paper seeks to advance this debate by addressing the questions of how the emancipatory potential of critical realism can be realised and how it may contribute to critical accounting research. In doing so, I draw on recent developments in critical realist thought which attempt to reconcile its ontological foundations with those of other social theorists, such as Giddens, Bourdieu and Foucault. This leads to an ontological synthesis pivoting on the interplay between exogenous structures, which reflect the objective life conditions of individual human beings, and endogenous structures, which condition their subjective capacity for reflexivity. I elaborate on how this interplay gives rise to a highly contingent conception of the possibilities of emancipation and examine the extent to which such a view is evident in critical realist accounting research and cognate bodies of critical accounting scholarship. I also examine the epistemological and methodological implications of adopting such a view and how critical research interventions in accounting, centred on the critical realist notion of explanatory critique, can be matched with the contingent possibilities of emancipation. I argue that such critiques can make a valuable contribution to critical accounting research as they compel researchers to go considerably beyond what is immediately observable and probe into the deeper structural conditions that constrain as well as enable emancipation. This may enable accounting scholars to envisage a broader range of alternative, but previously unrecognised, paths towards emancipation. It also provides a counterweight to empiricist modes of explanation, primarily based on observed regularities in social phenomena, which arguably tend to dominate contemporary policy debates.